Mutational Analysis of KCNQ1 Gene in Type 2 Diabetes Mellitus: A Case-control Study - Ankush Ganjewar; Ishwar B Bagoji; Sharan Badiger; Rudragouda B Bulagouda; Gurushnatappa Kadakol (Journal of Clinical and Diagnostic Research)
Introduction: KCNQ1 (Potassium voltage-gated channel subfamily Q member 1) gene encodes for pore-forming subunit of a voltage-gated K+ channel that is essential for the depolarisation phase of the action potential in cardiac muscle. KCNQ1 is also associated with impaired insulin secretion in Type 2 Diabetes Mellitus (T2DM), suggesting that this impairment might underlie the diabetes susceptibility conferred by rs151290, which is associated with 30-min C-peptide levels during an Oral Glucose Tolerance Test (OGTT) and first-phase insulin secretion. Variants rs2237892, rs2237895 and rs2237897 have been associated with OGTT-derived insulin secretion indexes. The risk associated with KCNQ1 may increase the expression of KCNQ1 in pancreatic β cells, promoting the development of T2DM. Aim: To know the association of KCNQ1 gene common variant rs2237895 risk factor for T2DM. Materials and Methods: The present case-control study was conducted at the Department of General Medicine and Genetics Laboratory of the Anatomy Department at BLDE (Deemed to be University) Shri BM Patil Medical College Hospital and Research Centre in Vijayapura, Karnataka, India. The duration of present study was from March 2023 to December 2023. A total of 30 peripheral blood samples were collected from the T2DM and 30 samples of healthy controls, and then subjected to genetic analysis. Amplification of DNA products were analysed using Sanger-based DNA sequencing. Results: Sequencing analysis revealed g.6956 C>T and c.C1956T mutations in seven patients. Out of these, three were in homozygous condition and four were in heterozygous condition. All these mutations were observed in 3’ untranslated region and exhibited a benign phenotype. Conclusion: KCNQ1 gene is not associated with Type 2 DM. To establish a definitive association between the KCNQ1 gene and T2DM, further screening in larger population is necessary.